KAJIAN KIMIA TANAH DI HUTAN PENDIDIKAN (KHDTK) UNIVERSITAS MUHAMMADIYAH PALANGKARAYA - Nurul Hidayati; Siti Maimunah; Nanang Hanafi (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2017)
This study aims to determine the level of soil fertility in terms of chemical kriteria soil in forest areas with special purpose. From this study, information about the condition of the land, as consideration in the context of the assessment and soil conservation efforts to be undertaken in the future. The research was conducted in September 2015 to November 2105, in the forest area with special purpose (KHDTK) UMP Mungku Baru Village Rakumpit District of the city of Palangkaraya. Object of research, namely land under forest stands, by: (a) take samples of the soil in the topsoil at a depth of between 0-20 cm (above), 20-30 cm (the middle one), 30-60 cm (center 2), and 70-100 cm (in), land was taken in composites, soil samples were taken at each distance + 1 meter direction of the wind, then mixed and stirred evenly (composite), then taken of approximately 1 kg to be analyzed in laboratory, and (b) as many as four soil samples have been taken and then dinalisis in the laboratory for chemical soil properties known circumstances. The results of soil analysis compared with the assessment criteria of physical and chemical properties of land according to the Institute for Land Research Center, Bogor, the Status fertility of the soil at a depth of 0-30 cm is moderate to high, while the planting depth 30-60 cm of low fertility, although the contribution of organic materials from the vegetation on it high.